Disease‐Modifying Anti‐Alzheimer's Drugs: Inhibitors of Human Cholinesterases Interfering with β‐Amyloid Aggregation. (July 2014) - Brogi, Simone; Butini, Stefania; Maramai, Samuele; Colombo, Raffaella; Verga, Laura; Lanni, Cristina; De Lorenzi, Ersilia; Lamponi, Stefania; Andreassi, Marco; Bartolini, Manuela; Andrisano, Vincenza; Novellino, Ettore; et al.
Summary Aims We recently described multifunctional tools (2a–c) as potent inhibitors of human Cholinesterases (ChEs) also able to modulate events correlated with Aβ aggregation. We herein propose a thorough biological and computational analysis aiming at understanding their mechanism of action at the molecular level. Methods We determined the inhibitory potency of 2a–c on Aβ1–42 self‐aggregation, the interference of 2a with the toxic Aβ oligomeric species and with the postaggregation states by capillary electrophoresis analysis and transmission electron microscopy. The modulation of Aβ toxicity was assessed for 2a and 2b on human neuroblastoma cells. The key interactions of 2a with Aβ and with the Aβ‐preformed fibrils were computationally analyzed. 2a–c toxicity profile was also assessed (human hepatocytes and mouse fibroblasts). Results Our prototypical pluripotent analogue 2a interferes with Aβ oligomerization process thus reducing Aβ oligomers‐mediated toxicity in human neuroblastoma cells. 2a also disrupts preformed fibrils. Computational studies highlighted the bases governing the diversified activities of 2a. Conclusion Converging analytical, biological, and in silico data explained the mechanism of action of 2a on Aβ1–42 oligomers formation and against Aβ‐preformed fibrils. This evidence, combined with toxicity data, will orient the future design of safer analogues.